Using the Internet to Conduct College Credit Courses Developed From Extension Materials - James M. Nehiley (Journal of Applied Communications, 1998)
A study was conducted at the University of Florida to determine whether an Internet writing course would be useful for teaching as a distance learning option. In this study, students located at off-campus, agricultural research centers enrolled in a Web-based composition course instead of a correspondence course to meet the writing requirements necessary for their graduation. The course used 22 modules on an Internet Web site that students visited instead of attending traditional classroom lectures. Students were required to have an Internet-accessing computer, and they were allowed to complete scheduled assignments at their own speed. Each student read the modules, answered questions included at the end of the text, and then sent the answers to the instructor to show that they had read the module and understood it. There were fifteen writing assignments, and each student was subsequently graded on how he or she used the techniques demonstrated in the modules to complete each assignment. After completing each assignment, the student sent it to the instructor via Internet mail where it was graded, marked in the text, and returned by the instructor. All communication between the instructor and the students was conducted via Internet mail. The study found that students who participated via the Internet submitted papers that were not as complete or as well-organized as those students participating in the classroom situation.